Interaction of behavior and physiology of anurans in response to thermal and hydric stress: an approach to understand the vulnerability of anurans to climate change - Molina, Estefany Caroline Guevara (2019)
In this master thesis, the thermoregulation model proposed by Heath (1970) was updated, integrating the effects of the hydration level on the thermoregulation behavior and the thermal tolerance limits of the Bull Frog, Lithobates catesbeianus (Chapter I). For the thermoregulation behavior the preferred body temperatures (PBT) of hydrated and dehydrated individuals were measured, and as thermal tolerance, the Voluntary Thermal Maximum (VTMax) and the Critical Thermal Maximum (CTMax) were measured in groups of individuals with different hydration levels. Chapter II uses the information collected in chapter I to evaluate the effects of the hydration level on the time to loss the locomotor function of L.catesbeianus individuals exposed to their VTMax. Both chapters indicates that dehydration negatively affects not only the thermoregulation behavior and thermal tolerance of this species, but also the time it takes for individuals to lose their locomotor function when exposed to their VTMax. Our data suggest that dehydration is an important variable that must be included to evaluate the effects of high temperatures and dry conditions on wet skin ectotherms. The temperature-dehydration integration and its effects on these organisms can be included in mechanistic distribution models to update their climate vulnerability under current and future scenarios of climate change